IMPLEMENTASI PROGRAM BANTUAN OPERASIONAL SEKOLAH (BOS) DI SMP NEGERI 2 SEMARANG - Ines Delaney Natasha; Aufarul Marom; Dewi Rostyaningsih (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2015)
Education is a major factor for a nation in order to carry out the construction. Seeing the importance of education for a nation, takes the role of government to meet the needs of the community. One of the efforts made by the government through the Ministry of Education and Culture of the Republic of Indonesia is a program of the School Operational Assistance or BOS. BOS Program is a program that supports the 9-year compulsory education program, in which each learner exempt from all operational costs of education. The research was conducted in SMP Negeri 2 Semarang and was based on the fact that in its implementation, still there are problems such as limited use of the funds for the school, as the executor. The purpose of this study is to describe and analyze the implementation of the School Operational Assistance (BOS) in SMP 2 Semarang and describe the driving factors and obstacles in the implementation of the Program School Operational Assistance (BOS) in SMP 2 Semarang. Based on research, the implementation of the School Operational Assistance (BOS) in SMP 2 Semarang is still not optimal. Therefore, the recommendations can be given is to not restrict the use of funds for each school, differences in the percentage of acceptance of funds received by schools based on the needs of each school, and the preparation of JUKNIS BOS not too stiff to use BOS funds can be more optimally.